IMPLEMENTASI EXPERIENTIAL MARKETING DAN INSTAGRAM UNTUK MENINGKATKAN VOLUME PENJUALAN PADA SEJAHTERA HATI WARUNG KOPI MADIUN - Candra Dyah Utami; Ajeng Wahyuni (Niqosiya: Journal of Economics and Business Research, 2022)
Experiential marketing has been widely applied to cafes as a marketing strategy. Likewise, marketing using social media Instagram is no stranger to the business world. However, the use of these two things is not always successful. Sejahtera Hati coffee shop is one of the cafes that was established during the covid-19 pandemic, at which time many business actors experienced setbacks or even went out of business. By implementing experiential marketing and promotions through Instagram, which is said to be very simple, coffee shops can thrive during a pandemic. The purpose of this study was to describe the implementation of experiential marketing in the prosperous liver of coffee shops, to find out the promotional strategies through social media Instagram that were applied by the prosperous hearts of coffee shops, and to know the impact of the application of experiential marketing and Instagram as promotional media in an effort to increase sales volume on prosperous hearts. coffee shop. The type of research used is filed research with a qualitative approach. Data collection techniques were carried out using the interview method, and also observation. Interviews were conducted with eight respondents, namely the owner, two employees, and also five visitors from the Prosperous Heart coffee shop. Data analysis techniques in this research are data reduction, data presentation, drawing conclusions or verification, and also checking the validity of the data. The result of this research is that the Prosperous Heart of the coffee shop has implemented experiential marketing starting from the dimensions of sense, feel, think, act, and relate. The promotion strategy for the Prosperous Heart of a coffee shop through Instagram media is by consistently uploading content through Instagram stories, and also reels, as well as maintaining good relations with customers through social media. The implementation of experiential marketing and Instagram as promotional media has a positive impact on the sales volume of the Prosperous Heart of the coffee shop. ABSTRAK Experiential marketing sudah banyak diterapkan pada cafe sebagai strategi pemasaran. Begitu juga pemasaran menggunakan media sosial instagram yang sudah tidak asing dalam dunia bisnis. Akan tetapi penggunaan kedua hal tersebut tidak selalu berhasil. Sejahtera hati warug kopi merupakan salah satu cafe yang berdiri pada masa pandemi covid-19 yang mana pada saat itu banyak pelaku usaha yang mengalami kemunduran atau bahkan gulung tikar. Dengan menerapkan experiential marketing dan promosi melalui media instagram yang dibilang masih sangat sederhana, sejahtera hati warung kopi dapat berkembang pada masa pandemi. Tujuan penelitian ini adalah untuk mendeskripsikan implementasi experiential marketing pada sejahtera hati warung kopi, mengetahui strategi promosi melalui media sosial instagram yang diterapkan oleh sejahtera hati warung kopi, serta mengetahui dampak dari penerapan experiential marketing dan instagram sebagai media promosi dalam upaya meningkatkan volume penjualan pada sejahtera hati warung kopi. Jenis penelitian yang digunakan adalah filed research dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan dengan menggunakan metode wawancara, dan juga observasi. Wawancara dilakukan kepada delapan responden yaitu owner, dua karyawan, dan juga lima pengunjung dari sejahtera hati warung kopi. Teknik analisis data dalam peneitian ini yaitu dengan cara reduksi data, penyajian data, menarik kesimpulan atau verifikasi, dan juga pengecekan keabsahan data. Hasil dari penelitian ini bahwa sejahtera hati warung kopi telah menerapkan experiential marketing mulai dari dimensi sense, feel, think, act, dan relate. Strategi promosi sejahtera hati warung kopi melalui media instagram yaitu dengan cara konsisten mengunggah konten melalui instagram story, dan juga reels, serta menjaga hubungan baik dengan pelanggan melalui media sosial. Implementasi experiential marketing dan instagram sebagai media promosi berdampak positif terhadap volume penjualan dari sejahtera hati warung kopi.